Experimenting biochemical oxygen demand decay rates of Malaysian river water in a laboratory flume - Nuruzzaman, Md.; Mamun, Abdullah Al; Salleh, Md. Noor (Korean Society of Environmental Engineers, 2018)
Lack of information on the Biochemical Oxygen Demand (BOD) decay rates of river water under the tropical environment has triggered this study with an aim to fill the gap. Raw sewage, treated sewage, river water and tap water were mixed in different proportions to represent river water receiving varying amounts and types of wastewater and fed in a laboratory flume in batch mode. Water samples were recirculated in the flume for 30 hours and BOD and Carbonaceous BOD (CBOD) concentrations were measured at least six times. Decay rates were obtained by fitting the measured data in the first order kinetic equation. After conducting 12 experiments, the range of BOD and CBOD decay rates were found to be 0.191 to 0.92 per day and 0.107 to 0.875 per day, respectively. Median decay rates were 0.344 and 0.258 per day for BOD and CBOD, respectively, which are slightly higher than the reported values in literatures. A relationship between CBOD decay rate and BOD decay rate is proposed as k_CBOD=〖0.8642k〗_BOD-0.0349 where, kCBOD is CBOD decay rate and kBOD is BOD decay rate. The equation can be useful to extrapolate either of the decay rates when any of the rates is unknown.